A student solved an equation, as shown below.


Based on the student's work, complete the statement below.
Use the drop-down menus to make the statement below true.

(8-12x)=x-2(2x+1)
2-3x=x-4x+2
2-3x = -3x+2
2-3x+3x = -3x+3x+2
2=2
The student solved the equation
A. Correctly B. Incorrectly

* 



because the original equation has
A. No solution
B. One solution
C. Infinitely many solutions

1 answer

The student solved the equation B. Incorrectly because the original equation has A. No solution.
Similar Questions
  1. A student solved an equation, as shown below.Based on the student's work, complete the statement below. Use the drop-down menus
    1. answers icon 1 answer
  2. A student solved an equation, as shown below.1/4(8-12x)=x-2(2x+1) 2-3x=x-4x+2 2-3x=-3x+2 2-3x+3x=-3x+3x+2 2=2 Based on the
    1. answers icon 1 answer
  3. A student solved an equation, as shown below1/4(8-12x) =x-2(2x+1) 2-3x = x-4x+2 2-3x=-3x+2 2-3x+3x = -3x+3x+2 2=2 Based on the
    1. answers icon 1 answer
    1. answers icon 1 answer
more similar questions